2020
DOI: 10.1016/j.psj.2020.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella enterica on poultry processing equipment after completion of sanitization procedures

Abstract: Salmonella is a poultry-borne pathogen that causes illness throughout the world. Consequently, it is critical to control Salmonella during the process of converting broilers to poultry meat. Sanitization of a poultry processing facility, including processing equipment, is a crucial control measure that is utilized by poultry integrators. However, prevalence of Salmonella on equipment after sanitization and its potential risk to food safety has not been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 50 publications
5
17
0
1
Order By: Relevance
“…Salmonella prevalence in carcass rinses has been reported as high as 54.09% [ 19 ]. A survey of 15 broiler processing plants indicated that even after sanitization procedures, Salmonella prevalence remained at a range of 7.4% to 29.69% [ 20 ]. A research study indicated that 7% of poultry origin Salmonella isolates in the southeastern United States exhibited resistance to at least one antimicrobial [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella prevalence in carcass rinses has been reported as high as 54.09% [ 19 ]. A survey of 15 broiler processing plants indicated that even after sanitization procedures, Salmonella prevalence remained at a range of 7.4% to 29.69% [ 20 ]. A research study indicated that 7% of poultry origin Salmonella isolates in the southeastern United States exhibited resistance to at least one antimicrobial [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contamination and cross‐contamination of workers, equipment and air can affect the further processing stages for chicken carcasses, with cleaning and disinfection procedures often being insufficient to eliminate bacteria contamination between working days, as shown for pathogens (Samapundo et al., 2019; Obe et al., 2020). Feathers may also act as a means of introducing antimicrobial contamination into the poultry slaughter process, despite the approved withdrawal period for medications being observed (Cornejo et al., 2018).…”
Section: Appendix E – Sources and Transmission Routes Additional Information For Terrestrial Animals And Aquaculture Productionmentioning
confidence: 99%
“…Hygiene and disinfection in transport and lairage (Mannion et al., 2008; Walia et al., 2017) together with management measures such as strict separation of animal batches, which can be extended to slaughter practices (Kudirkien≐ et al., 2011; Obe et al., 2020) may reduce the spread of ARB in these two stages. For disinfection, the appropriate choice of biocides, their concentration and application rate, validation and regular testing and potentially the rotation of biocide classes are of relevance.…”
Section: Assessmentmentioning
confidence: 99%
“…Serovar‐to‐serovar differences can create challenges in eliminating Salmonella during poultry processing, and it is possible that processing interventions are selecting for phenotypic differences. Many recent studies have suggested that some Salmonella serovars can survive processing interventions and some can persist in the environment (Eastwood et al, 2021; Mourão et al, 2020; Obe et al, 2020). For example, the susceptibility of several Salmonella isolates in different serovars were evaluated and Salmonella serovars Enteritidis and Typhimurium showed the most resistance to benzalkonium chloride, a quaternary ammonium compound (Long et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella can attach and produce biofilm on different surfaces, including stainless steel and plastic, which are commonly found in the poultry processing environment (Lee et al, 2020; Veluz et al, 2012). This allows Salmonella to persist in processing environments and subsequently contaminate products (Obe et al, 2020). Since bacteria produce biofilm under stressful conditions, many studies have investigated the biofilm‐forming capacity of Salmonella under different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%